Role of lysosome in healing neurological disorders by nano-bioengineering - Raj, Aiswarya; Bandyopadhyay, Urmi (Frontiers in Neuroscience, 2024)
Lysosomes primarily recognized as center for cellular 'garbage-disposing-unit', which has recently emerged as a crucial regulator of cellular metabolism. This organelle is a well-known vital player in the pathology including neurodegenerative-disorders [1]. In pathological context, removal of intracellular damaged misfolded proteins, organelles and aggregates are ensured by 'Autophagy' pathway, which initially recognizes, engulfs and seals the toxic cargo at the cytosolic environment. Thereafter the cell completes the task of encapsulated cargo elimination upon delivery of them to the terminal compartment -lysosome, which contains acid hydrolases, that are capable of degrading the abnormal protein-lipid-repertoire. The merge between inseparable 'Autophagy' and 'Lysosomal' pathways evolved into 'Autophagy-Lysosome Pathway (ALP)', through which cell ultimately degrades and recycles bio-materials for metabolic needs. Dysregulation of any of the steps of the multi-step ALP can contribute to the development and progression of disorders including Alzheimer's Disease (AD), Parkinson's Disease (PD), and Huntington's Disease (HD). Therefore, targeting differential steps of ALP or directly lysosomes using nano-bioengineering approaches holds great promise for therapeutic interventions. This review aims to explore the role of distal autophagy pathway and proximal lysosomal function, as cellular degradative and metabolic hubs, in healing neurological disorders and highlights the contributions of nano-bioengineering in this field. Despite multiple challenges, this review underscores the immense potential of integrating autophagy-lysosomal biology with nanobioengineering to revolutionize the field and provide novel therapeutic avenues for tackling neurological-neurodegenerative-disorders.